Entrepreneurship in Haiti: Toward an Identification of The ‘Blind Spots’ - Vanessa Gowreesunkar; Hugues Séraphin (Études Caribéennes)
In countries that have experienced abusive power relationships, ongoing poverty, prejudice, violence and natural disaster, changes hardly happen and if they do, they are very slow. Haiti is not an exception. The problem of entrepreneurship in Haiti goes beyond human management and business management skills. It is first of all a human issue: The primary needs of the locals need to be met; a sense of community needs to be developed and the locals need to be able to dream; and finally, the right context needs to be put in place and the ‘yes, we can spirit’ encouraged. It is the improvement of the well-being of Haitians that is going to lead to the development of a strong entreprrenurial system. It is a one way relationship. In poor countries like Haiti it is important to address the human condition first. Unlocking change through: transformational leadership; enterprise reform; technology innovation; corporate transparency; stakeholders engagement; social responsibility; integrated value and finally, through future-fitness could be a potential option for Haiti.